Outcomes of infected grade IIIB open tibial fractures - Mohd Yusof, Nazri; Halim, Ahmad Sukari (Singapore Medical Association, 2012)
Introduction Infection following grade IIIB open tibial fracture is common. The primary aim of managing this condition is to achieve control of infection before the bone reconstruction procedure is performed. The outcomes for such patients have not been evaluated in the literature. This study was conducted to examine the outcome of a multistage procedure for the treatment of infected grade IIIB open tibial fractures. Methods Between 2004 and 2008, we treated 11 patients with infected grade IIIB open tibial fractures in our unit. The management of infected grade IIIB open tibial fracture comprised three stages, which included serial debridement, wound closure by local flap surgery and bone reconstruction. The margin of resection and the type of bone reconstruction depended on the anatomical location of the disease, the extent of osteomyelitis and patient preference regarding treatment options. Bone reconstruction procedures included bone grafting, plating, interlocking nail, hybrid and monolateral external fixator, and Ilizarov bone transport. Resu lts Gram-negative organisms were isolated from all patients. Pseudomonas aeruginosa (P. aeruginosa) (44%) was the most common organism cultured. Infection was resolved in all patients. Nine fractures achieved union, with a mean union time of 15 months. Two patients with P. aeruginosa infection developed non-union of the fracture and refused additional surgery after three years of treatment. Conclusion The multi-stage management approach is well-accepted and effective in controlling infection in infected grade IIIB open tibial fractures.